2018
DOI: 10.5194/tc-2018-132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of four calving laws to model Greenland outlet glaciers

Abstract: Abstract. Calving is an important mechanism that controls the dynamics of marine terminating glaciers of Greenland. Iceberg calving at the terminus affects the entire stress regime of outlet glaciers, which may lead to further retreat and ice flow acceleration. It is therefore critical to accurately parameterize calving in ice sheet models in order to improve the projections of ice sheet change over the coming decades and reduce the uncertainty in their contribution to sea level rise. Several calving laws have… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Based on the above considerations, the von Mises and von Mises tensile stresses produce the most realistic calving front geometry evolutions for tidewater glaciers using a continuum damage mechanics model. This observation agrees with results from Choi et al (), who found that the von Mises tensile stress provides more satisfactory results than the three other calving laws in their comparison effort.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the above considerations, the von Mises and von Mises tensile stresses produce the most realistic calving front geometry evolutions for tidewater glaciers using a continuum damage mechanics model. This observation agrees with results from Choi et al (), who found that the von Mises tensile stress provides more satisfactory results than the three other calving laws in their comparison effort.…”
Section: Discussionsupporting
confidence: 92%
“…The presented model was implemented in plane‐strain formulation in a vertical section along the flow line. Consequently, important effects such as lateral stress bridging are neglected (Choi et al, ; Todd et al, ). The current model implementation is generic and can be used in three dimensions by only changing the finite element types to three‐dimensional hexahedral or tetrahedral elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter periods are more prone to noisy results, but offer higher temporal resolution, while an increase in temporal integration time smoothens the results. to the operational products) which affects observational constraints for models of flow dynamics of calving and our understanding of terminus dynamics (Nick et al, 2009Choi et al, 2018;Morlighem et al, 2017;King et al, 2018).…”
Section: Comparison To Operational Ice Velocity Productsmentioning
confidence: 99%
“…First, there is still debate on how to parameterize important processes like submarine terminus melt, calving, and basal sliding. The recent surge of new observational data around the GrIS has enabled observation‐based testing of a number of existing process parameterizations that control glacier flow (Bondzio et al, ; Choi et al, ; Choi et al, ; Enderlin & Bartholomaus, ; Stearns & van der Veen, ), but these must be generalized across all glacier systems and validated with observations. Second, improvements in model resolution and nested modeling techniques are beginning to allow full ice sheet models to resolve outlet glaciers (Aschwanden et al, ; Aschwanden et al, ), but resolution challenges continue.…”
Section: Future Research Needsmentioning
confidence: 99%